2019
DOI: 10.1055/a-1007-1995
|View full text |Cite
|
Sign up to set email alerts
|

Design und Evaluation eines Prüf-Studierenden-Kurses für studentische prospektive Multicenterstudien – ein CHIR-Net-SIGMA-Projekt zum forschenden Lernen

Abstract: Zusammenfassung Hintergrund Die Vermittlung wissenschaftlicher Kompetenzen im Medizinstudium ist mangelhaft. Dies setzt sich in der Weiterbildung fort und führt zunehmend zu einem Mangel an wissenschaftlich tätigen Ärzten. Das chirurgische Studiennetzwerk (CHIR-Net) hat ein studentisches Forschungsnetzwerk gegründet (SIGMA, Student-initiated German Medical Audit), um dem entgegenzuwirken. Ziel dieser Arbeit ist es, die Entwicklung, Umsetzung und Evaluation eines Prüf-Studierenden-Kurses (PSK) zu besc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…In addition, query management and response need to be part of the pre-study training workshop. 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, query management and response need to be part of the pre-study training workshop. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Participating medical students are trained in workshops to acquire the theoretical and practical know-how to conduct substantial parts of clinical studies independently and act as peer-teachers for fellow students. 20 Data analyses, interpretation, and reporting are performed by student members under the auspices of statisticians and CHIR- Net facilitators. PATRONUS is the first clinical study of the SIGMA study group.…”
Section: Methodsmentioning
confidence: 99%
“…Research-based learning is a concept that refers to a trend in higher education: to provide students with the opportunity to gain knowledge by conducting their own scientific inquiries or investigations [32]. In 2017 the study network of the German Surgical Society (CHIR-Net [33];) founded a student-led clinical trial network across Germany (SIGMA; Student-Initiated German Medical Audit, [34]) [35,36]. SIGMA has performed an observational study investigating patient-reported outcome measures and complications after surgery [37] and will perform the EXPELLIARMUS trial.…”
Section: Student-led Clinical Researchmentioning
confidence: 99%
“…In order to standardise outcome assessment, medical students are trained during a clinical investigator training (CIT) course in study-specific procedures as well as good clinical practice to reduce detection bias. The curriculum of the CIT has been described elsewhere [36]. Furthermore, obligatory online training material is available to all participating students.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Die in dieser Ausgabe des Zentralblatt für Chirurgie vorgestellte CHIR-Net-Sigma-Studie [1] untersucht, wie in der zunehmenden Fokussierung auf die klinischen Aspekte in den Universitätsklinika Studierenden auch bereits während des Medizinstudiums wissenschaftliche Kompetenzen vermittelt werden können. Der hier vorgestellte Prüf-Studierenden-Kurs im Rahmen des CHIR-Net-Sigma-Projektes zeigt, dass eine Ausbildung von Medizinstudierenden die eigenständige Durchführung von klinischen Studien effizient vorbereiten kann.…”
unclassified